A Community-Driven Approach to Identifying â€œWinnableâ€? Policies Using the Centers for Disease Control and Preventionâ€™s Common Community Measures for Obesity Prevention - Jilcott Pitts, Stephanie Bell; Whetstone, Lauren M.; Wilkerson, Jean R.; Smith, Tosha W.; Ammerman, Alice S. (My University, 2012)
Federally funded, community-based participatory research initiatives encourage the development and implementation of obesity prevention policies. In 2009, the Centers for Disease Control and Prevention (CDC) published the Common Community Measures for Obesity Prevention (COCOMO), which include recommended strategies and measures to guide communities in identifying and evaluating environmental and policy strategies to prevent obesity. Agreeing on "winnable" policy issues can be challenging for community members. We used CDC's COCOMO to structure in-depth interviews and group discussions with local stakeholders (ie, planners, town managers, and a local community advisory council) to stimulate interest in and identify health-promoting policies for local policy and planning agendas. We first asked stakeholders to rank the COCOMO recommendations according to feasibility and likelihood of success given community culture, infrastructure, extent of leadership support, and likely funding support. Rankings were used to identify the most and least "winnable" COCOMO policy strategies. We then used questions from the evidence-based Community Readiness Handbook to aid discussion with stakeholders on the facilitators and barriers to enacting the most and least winnable policy options identified. Finally, we discuss potential adaptations to COCOMO for rural jurisdictions.